Hostplant Availability Influences Colonization Patterns and Pre-adult Development of Pachliopta antiphus antiphus in an Urban Ecotone in Palembang, Indonesia : Integrating Oviposition Behavior, Larval Development, and Resource Availability - Ina Aprillia; Guntur Pragustiandi; Muhammad Iqbal (BIOVALENTIA: Biological Research Journal, 2026)
Hostplant availability is a key factor influencing butterfly distribution, particularly in urban environments with limited ecological resources. This study aimed to examine the colonization, oviposition behavior, and pre-adult development of Pachliopta antiphus antiphus following the introduction of its host plant Aristolochia tagala in a residential area in Palembang, Indonesia. A direct observation method was applied to monitor butterfly presence, egg-laying activity, and development from egg to adult stage. All observed individuals  (total of 12 eggs successfully developed into adults. Eggs were laid singly, primarily on young leaves. Larval development consisted of four instars, with increasing body size and feeding rate at each stage. The duration from egg to adult emergence fell within the normal developmental range reported for the genus. This finding highlights the importance of hostplant presence in supporting butterfly persistence and suggests a nested pattern of species occurrence within urban landscapes.